1996
DOI: 10.1002/recl.19961150206
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric induction in kinetically controlled zirconium‐catalysed Meerwein‐Ponndorf‐Verley reductions

Abstract: Twelve chiral ligands 718 were tested in the new kinetically controlled variation of zirconium alkoxide catalysed Meerwein-Ponndorf-Verley reduction of 2'-chloroacetophenone (2) using rac-4 as the reducing alcohol (Scheme 3). The tetraaryl-1,3-dioxolanes 11 (ca. 30% enantiomeric excess, ee) and the triphenylethanediol 14 (62% ee, 99% yield) gave the best results. A relatively low dependence on the amount of the catalyst (aluminum alkoxide gave no asymmetric induction) and the ligand excess was observed compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Consistent with aggregation of the catalyst is the concentration-dependence and inverse temperature-dependence of induction, with different enantiomers being preferentially produced at 0 "C and -23 "C. The optimum catalyst 17 was found to give 87 YO ee for the reaction of cinnamaldehyde and ketene acetal 10. The same catalyst gave 80:20 anti:syn selectivity from the reaction of benzaldehyde and the ketene acetal 22 where the major anti isomer was produced with YO YO ee. Finally, it was observed that catalyst 17 was ineffective at producing a reaction between aldehydes and ketene acetal25 (Sch.…”
Section: Aldol Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with aggregation of the catalyst is the concentration-dependence and inverse temperature-dependence of induction, with different enantiomers being preferentially produced at 0 "C and -23 "C. The optimum catalyst 17 was found to give 87 YO ee for the reaction of cinnamaldehyde and ketene acetal 10. The same catalyst gave 80:20 anti:syn selectivity from the reaction of benzaldehyde and the ketene acetal 22 where the major anti isomer was produced with YO YO ee. Finally, it was observed that catalyst 17 was ineffective at producing a reaction between aldehydes and ketene acetal25 (Sch.…”
Section: Aldol Reactionsmentioning
confidence: 99%
“…Slightly higher induction was observed with chiral alkoxides derived from erbium iso-propoxide but the reactions were still not synthetically useful. Finally, Krohn and Knauer have reported that a catalyst prepared from a TADDOL ligand and aluminum tert-butoxide failed to give any asymmetric induction in a MeerweinPonndorf-Verley reduction [22] Asymmetric reduction of carbonyls has also been achieved by Dupas and coworkers by reaction of achiral NADH equivalents mediated by chiral aluminum Lewis acids [23]. They reduced methyl benzoyl formate with the dihydropyrido[2,3-b]indole 86 and chiral aluminum Lewis acids whose structures are drawn and 89 and 90 (Sch.…”
Section: Carbonyl Additions and Reductionsmentioning
confidence: 99%